2020
DOI: 10.1111/cts.12921
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoenhancement of Low Crizotinib Plasma Concentrations in Patients with Anaplastic Lymphoma Kinase‐Positive Non‐Small Cell Lung Cancer using the CYP3A Inhibitor Cobicistat

Abstract: The inhibitor of anaplastic lymphoma kinase (ALK) crizotinib significantly increases survival in patients with ALK-positive non-small cell lung cancer (NSCLC). When evaluating crizotinib pharmacokinetics (PKs) in patients taking the standard flat oral dose of 250 mg b.i.d., interindividual PK variability is substantial and patient survival is lower in the quartile with the lowest steady-state trough plasma concentrations (C min,ss), suggesting that concentrations should be monitored and doses individualized. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…ZINC8214703, namely, unoprostone, could reduce intraocular pressure and treat glaucoma [ 47 ]. ZINC85537014, namely, cobicistat, has the ability to treat human immunodeficiency virus (HIV) infection [ 48 ] and increase the response rates of anticancer drugs [ 49 ]. Because of the anticancer properties of iloprost and unoprostone, these two small molecules might be new drug candidates for TSCC patients [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…ZINC8214703, namely, unoprostone, could reduce intraocular pressure and treat glaucoma [ 47 ]. ZINC85537014, namely, cobicistat, has the ability to treat human immunodeficiency virus (HIV) infection [ 48 ] and increase the response rates of anticancer drugs [ 49 ]. Because of the anticancer properties of iloprost and unoprostone, these two small molecules might be new drug candidates for TSCC patients [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical trial was terminated because of the approval of alectinib, a next‐generation ALK inhibitor. Nonetheless, in one patient, cobicistat increased crizotinib exposure with no adverse effects 56 . Together, these case studies suggest that cobicistat could boost levels of an oral TKI otherwise unlikely to benefit a patient due to physiologic barriers.…”
Section: Intentional Use Of Drug–drug Interactions To Increase Bioavailabilitymentioning
confidence: 81%
“…Two case studies have demonstrated that cobicistat, a potent and allegedly selective CYP3A inhibitor, 22 could boost drug levels of axitinib and crizotinib, respectively 55,56 . Axitinib is an oral multi‐kinase inhibitor metabolised by CYP3A that is approved by the FDA and EMA for metastatic renal cell carcinoma (mRCC).…”
Section: Intentional Use Of Drug–drug Interactions To Increase Bioavailabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there has been a growing interest in the use of this boosting concept as a strategy to improve the pharmacokinetic profile of TKIs already developed and marketed for oral use. Case studies have previously explored the use of cobicistat, to boost levels of TKIs including crizotinib (46) and axitinib (47). Another recent study reported the use of itraconazole, an antifungal drug that is less hepatotoxic than ketoconazole (8), to improve the systemic exposure to ibrutinib in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%